Rainfall and nest site competition delay Mountain Bluebird and Tree Swallow breeding but do not impact productivity. (21st February 2020) - Drake, Anna; Martin, Kathy
Abstract: Optimizing breeding phenology, an important aspect of fitness, is complex for migratory species as they must make key timing decisions early, and remotely, from breeding sites. We examined the role of weather (locally and cross-seasonally), cavity availability, and competitive exclusion in determining among-year variation in breeding phenology over 17 yr for 2 migratory, cavity-nesting birds: Mountain Bluebirds ( Sialia currucoides ; n = 462 nests) and Tree Swallows ( Tachycineta bicolor ; n = 572) using natural tree cavities in British Columbia, Canada. We assessed weather effects within the winter and migratory range and at our study sites. We quantified competition as the proportion of cavities occupied by European Starlings ( Sturnus vulgaris ) (for both species) and Mountain Bluebirds (for Tree Swallow only) in each year. For 229 bluebird and 177 swallow nests with known fates, we tested whether late years resulted in reduced productivity. Although the effects were small, heavy rainfall and strong diurnal westerly winds during migration were associated with breeding delays for Mountain Bluebirds. However, cavity availability (earlier breeding with increases) had a 5–8 × greater effect on timing than migratory conditions. There was no evidence that starling competition delayed bluebirds. In Tree Swallows, greater local daily rainfall was associated with delayed breeding, as was starling abundance (the effect of starlings was 1.4 × smaller than that of rainfall). Neither bluebird abundance nor cavity availability changed swallow phenology. Neither species showed reduced productivity in late breeding years. In both species, individuals that bred late relative to conspecifics within-year had smaller clutches and greater probability of nest failure. We conclude that breeding ground conditions, particularly cavity limitation and local rainfall (for swallows), are important drivers of breeding phenology for our focal species, but that the productivity cost of late years, at least for Tree Swallows, is minimal.